Physical examination in nurses' hospital practice (Research, Society and Development, 2020)
This study aimed to understand how physical examination occurs in nurses' hospital practice. It is a descriptive and exploratory research, with a qualitative approach. Eighteen nurses from the medical clinic of a public hospital unit, located in the state of Tocantins, Brazil, were interviewed. The collection took place through an open interview that took place in 2015. The data was analyzed according to the assumptions of the Content Analysis. This study was approved by the Permanent Education Center of the researched hospital and by the Human Research Ethics Committee under protocol 003/2015. Results: Two categories emerged: The moment of the physical examination in the nurse's practice is a limit to perform it, as there are other demands on the service and when it is done, it is upon the client's admission; and how the physical examination is performed in the nurse's practice, when it occurs, it is often not performed completely, as professionals do not feel with certain skills. Final Considerations: the time to perform the physical examination, the work overload, insufficient material resources and reduced technical knowledge and skills, imply the physical examination in the nurse's hospital practice.